Control interno y la productividad del personal de la empresa Nevada Entretenimientos Sociedad Anónima Cerrada Sala Iquitos periodo abril 2024 - Panduro Gómez de Yoshikawa, Nélida Miluska (2025)
The objectives of the research were to identify the relationship between internal control and the productivity of the staff of Nevada Entertainment Closed Joint Stock Company Iquitos Room, period April 2024, to identify if there is a relationship between the control environment and the productivity of the staff of Nevada Entertainment Closed Joint Stock Company Iquitos Room period April 2024, identify if there is a relationship between the risk assessment and the productivity of the staff of Nevada Entertainment Closed Public Limited Company Room Iquitos period April 2024, identify if there is a relationship between the activities and productivity of the staff of Nevada Entertainments Closed Joint Stock Company Iquitos Room period April 2024, identify if there is a relationship between the information and communication and the productivity of the staff of Nevada Entertainments Closed Joint Stock Company Iquitos Room period April 2024 and identify if there is a relationship between monitoring and the productivity of the staff of Nevada Entertainment Closed Joint Stock Company Iquitos Room period April 2024. The investigation It is applied, with a quantitative approach, correlational level and non-experimental design; The results demonstrate that there is a strong positive correlation between Internal Control and Productivity, with a Spearman correlation coefficient of 0.789 and a significance level of p = 0,000.